2011
DOI: 10.1021/ja1106282
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective [3 + 2] Cycloaddition of Allenes to Acrylates Catalyzed by Dipeptide-Derived Phosphines: Facile Creation of Functionalized Cyclopentenes Containing Quaternary Stereogenic Centers

Abstract: A new family of dipeptide-based chiral phosphines was designed and prepared. D-Thr-L-tert-Leu-derived catalyst 4c promoted [3 + 2] cycloaddition of allenoates to α-substituted acrylates in a regiospecific and stereoselective manner, furnishing functionalized cyclopentenes with quaternary stereogenic centers in high yields and with excellent enantioselectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
63
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 286 publications
(64 citation statements)
references
References 70 publications
1
63
0
Order By: Relevance
“…In this work, l-threonine-derived phosphine-thiourea catalyst 28 was shown to promote allylic alkylations of MBH carbonates with phthalides in a very high enantioselective manner. [29] In addition, consistent with their previous findings, [11] the hydrogen bonding interactions between the Brønsted acid moiety of the catalyst and the ester group of phthalide are crucial for the observed stereoselectivity. The threonine-derived phosphine catalysts containing bulky silicon-based group and thiourea motif proved to be privileged, in which the sterically hindered silyloxy groups were generally effective and triisopropylsilyl-protected phosphine catalyst 28 led to the best results.…”
Section: Allylic Alkylationssupporting
confidence: 84%
See 1 more Smart Citation
“…In this work, l-threonine-derived phosphine-thiourea catalyst 28 was shown to promote allylic alkylations of MBH carbonates with phthalides in a very high enantioselective manner. [29] In addition, consistent with their previous findings, [11] the hydrogen bonding interactions between the Brønsted acid moiety of the catalyst and the ester group of phthalide are crucial for the observed stereoselectivity. The threonine-derived phosphine catalysts containing bulky silicon-based group and thiourea motif proved to be privileged, in which the sterically hindered silyloxy groups were generally effective and triisopropylsilyl-protected phosphine catalyst 28 led to the best results.…”
Section: Allylic Alkylationssupporting
confidence: 84%
“…[11] Screening of different amino acid or dipeptide-derived chiral phosphines revealed that the d-Thr-ltert-Leu dipeptide backbone was the best, and the effect of the siloxyl groups were also palpable. In enamine or iminium catalysis, introduction of silicon-based bulky groups to amino catalysts has proved to be an effective strategy, which could enhance the catalytic efficiency and selectivity of the reaction.…”
Section: Chemcatchem Minireviewsmentioning
confidence: 99%
“…1b). In a separate study, Lu et al 22,23 reported the development of a phosphine catalysed [ [3 þ 2] cycloadditions of allenoates with electron-deficient olefins and imines-a process that provided efficient access to a variety of synthetically useful carbo-and hetereocycles-have received considerable research interest, and significant progresses have been elegantly demonstrated by different groups [24][25][26][27][28][29][30][31][32][33] As a useful nucleophile, allenyl metal species can react with a wide variety of electrophiles [34][35][36] and, consequently, these adducts have been applied to the syntheses of a broad range of structurally diverse compounds [37][38][39] . However, the use of allenyl rhodium species in organic synthesis remains scarce [40][41][42] .…”
mentioning
confidence: 99%
“…In 2011, Kwon reported the phosphinecatalyzed [4 + 3], [3 + 3] and [3 + 2] annulations of azomethine imines with allenoates with good yields at mild condition [29]. Besides, there are various kinds of phosphine-catalyzed annulation reactions, which are contributed to expand the applications in heterocycle synthesis [43][44][45][46][47][48][49][50][51][52][53][54].…”
Section: Introductionmentioning
confidence: 99%